Molecular mechanisms of tocotrienol-rich fraction and vitamin C in ameliorating oxidative stress in down syndrome / Maziana Mahamood - Mahamood, Maziana (2023)
Down syndrome (DS) is a common chromosomal abnormality occurring in about 1 in 700 live births. The gene encoding for Cu-Zn superoxide dismutase (SOD) is present on chromosome 21, thus, individuals with triplicates of this chromosome are postulated to be in a state of oxidative stress. Previously, it was shown that DS was associated with oxidative stress and impairment of immune function. It is postulated that the supplementation with tocotrienol rich fraction (TRF) (150 mg) and vitamin C (500 mg) will relieve DS subjects from oxidative stress i.e the improvement of the DNA damage levels, antioxidant-oxidative stress status, plasma levels of vitamin C and E and miRNA levels. This study aimed to examine the molecular mechanism of TRF and vitamin C to combat oxidative stress in DS. This was a cross-sectional study carried out with informed consent on DS subjectsfrom several Pusat Pemulihan Dalam Komuniti (PDK) in Klang Valley after ethical approval was obtained. The demographic data of the study participants were gathered through questionnaires that were distributed to parents. Sixty DS subjects (2 to 29 years old) were recruited and randomly assigned to receive either supplementation (n=30) with TRF (150 mg) and vitamin C (500 mg) or placebo (n=30), daily for 6 months. Blood samples were obtained from each subject at 0, 3rd and 6th months for the analysis. Antioxidant-oxidative stress status was assessed from the measurement of antioxidant enzyme activities in erythrocytes, viz, SOD, catalase (CAT) and glutathione peroxidase (GPx). DNA damage was measured using comet assay and 8-hydroxy-2’-deoxyguanosine (8-OHdG) level was evaluated using ELISA to measure the endogenous oxidative damage to DNA. The 8-isoprostane level was measured to study the biomarker of oxidative stress. Vitamin C and E levels were assessed using HPLC and miRNA analysis was performed using RT-PCR. This study showed the activities of antioxidant enzymes of DS subjects after supplementation with TRF and vitamin C were similar when comparing the baseline to 3 and 6 months (p>0.05). There were no associations between SOD, CAT and GPx activities and plasma level of vitamin C and E in treatment and control groups (p>0.05). There were no significant differences in the comet assay in treatment and control groups at 0, 3 and 6 months of supplementation (p>0.05). Increased plasma level of total vitamin E concentrations was observed with the duration of treatment, after 3 months (9.45±0.58 g/mol, p0.05) in the expression compared to baseline at 0 month. A significantly upregulated expression of hsa-miR-99a (2.40±0.08 folds, p=0.044) and hsa-miR-802a (3.60±0.041 folds, p=0.022) were seen compared to controls after 3 months of intervention. A significantly upregulated expression of hsa-miR-99a (2.58±0.04 folds, p=0.049) and downregulated expression of hsa-miR-125b (3.51±0.01 folds, p=0.049) were found compared to controls at 6 months of intervention. In conclusion, daily supplementation with TRF (150 mg) and vitamin C (500 mg) for 6 months did not improve the oxidative stress level in DS subjects. Factors such as the duration of supplementation and the number of subjects should be addressed in future studies. Other factors such as genetic, epigenetic, and environmental may play a role in how the DS phenotype specifically that related to oxidative stress expresses itself in each individual.